Self-Deception Reduces Cognitive Load: The Role of Involuntary Conscious Memory Impairment - Jian, Zengdan; Zhang, Wenjie; Tian, Ling; Fan, Wei; Zhong, Yiping (Frontiers in Psychology, 2019)
People often hear classic allusions such as plugging one's ears while stealing a bell, drawing cakes to satisfy one's hunger, and the emperor's new clothes. These allusions reflect a principle that people believe in nonexistent phenomena to satisfy their desires, also called self-deception. The current research used three experiments to examine the impact of social status and cognitive load on self-deception, and further to explore the inner connection about cognitive load and self-deception. The results found that deceiving individuals of high social status can play a role through the intrinsic mechanism of Involuntary Conscious Memory (ICM). The higher the cognitive load of the deceiver, the greater the possibility of deception. Our studies demonstrated that Involuntary Conscious Memory is the internal mechanism of self-deception, further explore the origin of self-deception, and enrich the self-deception theory.